2019
DOI: 10.1111/jpn.13168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local diets on nutritional and sensory quality of meat of indigenous goats in Tunisian arid regions

Abstract: The valorization of natural resources in small ruminants feeding can reduce the cost of feed and produce good meat quality. The objective was to evaluate the effects of local feed resources on the physico‐chemical aspects, the sensorial characteristics and the fatty acid profile of goat kid's meat. Twenty‐six kids are divided in three groups (average body weight = 15.85 kg; age = 4 months). The groups received oat hay (group control C), dried olive leaves + dried Stipa tenacissima (group OL) or grass hay (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In this study, the contents of essential amino acid of threonine (Thr) was lower and other two essential amino acids of valine (Val) and phenylalanine (Phe) were higher in Semimembranosus muscles of goats fed forage maize. This result was consistent with the observation that the amino acids profile of goat meat protein was significantly affected by diet ( 29 ). Overall, meats from goats fed forage maize, especially Semimembranosus muscles are rich in essential amino acids, can be good sources of proteins for humans.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the contents of essential amino acid of threonine (Thr) was lower and other two essential amino acids of valine (Val) and phenylalanine (Phe) were higher in Semimembranosus muscles of goats fed forage maize. This result was consistent with the observation that the amino acids profile of goat meat protein was significantly affected by diet ( 29 ). Overall, meats from goats fed forage maize, especially Semimembranosus muscles are rich in essential amino acids, can be good sources of proteins for humans.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with that in the control group, the L Ã value of the fermented Caragana korshinskii group was increased in the biceps femoris. Ayeb et al (2019) found that the meat colour parameters of the same breed of mutton, such as muscle redness (a value) and muscle yellowness (b value), were close to the average values, but the muscle brightness (L value) of lambs provided with supplementary feed was higher than that of lambs fed with the normal feeding method. Shen et al (2011) mainly studied the effects of biofermented feed on the growth and meat quality of Lulai black pigs at fattening.…”
Section: Discussionmentioning
confidence: 82%
“…Phenolic components have been evaluated to improve the physicochemical composition, FA profile, and sensory attributes of chevon [ 111 , 112 , 113 , 114 , 115 , 116 ]. It has been shown that supplementation of diets containing polyphenols positively improved the FA profile and reduced malondialdehyde concentration (a lipid oxidation substance) in chevon [ 117 ].…”
Section: Nutritional Effects On the Meat Of Sheep Goats And Cattlementioning
confidence: 99%
“…Dietary supplementation with polyphenol extract powder from olive mill water waste has improved unsaturated FA/SFA ratios in the meat of Saanen goats [ 117 ]. Using a mix of dried olive leaves and dried Stipa tenacissima has improved the ω-6/ω-3 ratio of meat of Tunisian indigenous goats [ 112 ]. It has been shown that the inclusion of 15% olive leaf into the diets changed the fatty acid composition and improved ω-6/ω-3 ratios in both muscle and adipose tissues of Mahabadi goats [ 114 ].…”
Section: Nutritional Effects On the Meat Of Sheep Goats And Cattlementioning
confidence: 99%